Combination of endosonography‐guided fine‐needle aspiration and conventional endoscopic techniques in sarcoidosis diagnosis. Optimal strategy to achieve high diagnostic yield. (23rd October 2020) - Kasper, Lukasz; Andrychiewicz, Anna; Gross‐Sondej, Iwona; Soja, Jerzy; Kasper, Marta; Tomaszewska, Romana; Urbanczyk, Katarzyna; Sladek, Krzysztof
Abstract: Introduction: Diagnosis of sarcoidosis is based on clinical status and radiologic specific findings. Tissue confirmation of noncaseating granulomas is crucial. Pathological confirmation of pulmonary sarcoidosis is most commonly accomplished by bronchoscopy, which has a diagnostic yield of approximately 60%–70%. Objectives: In this prospective study, we analysed potential benefit of EBUS‐TBNA and EBB combination, application of cell blocks and smears with puncturing more than one station of lymph nodes in order to determine optimal strategy in diagnosis of sarcoidosis. Methods: About 133 patients with suspicion of sarcoidosis (stage I and stage II) were included in this study. Each patient underwent conventional bronchoscopy with endobronchial biopsy (EBB) followed by the EBUS and puncturing at least two different lymph node stations. Results: Positive cytopathological verification of sarcoidosis in our study was obtained in 123 patients (92.5%). EBUS‐TBNA was diagnostic in 116 patients (87.2%). EBB was positive in 26 patients (19.55%). Combination of EBUS‐TBNA and EBB statistically increased diagnostic yield of sarcoidosis to 92.5%. Sensitivity of EBUS‐TBNA with EBB was 93.9%, specificity 100%, PPV 100% and NPV 20%. Conclusions: Combining EBUS‐TBNA from at least two lymph node stations and EBB increased diagnostic yield of sarcoidosis. Such diagnostic strategy had almost 93% of diagnostic yield in stage I and stage II of sarcoidosis. Taking into account the safety of the whole procedure with endobronchial ultrasonography combined with conventional endoscopy with EBB and its cost effectiveness, TBLB can be intended to diagnose stage III or IV of pulmonary sarcoidosis.